2019
DOI: 10.1088/1475-7516/2019/10/064
|View full text |Cite
|
Sign up to set email alerts
|

Can we distinguish black holes from naked singularities by the images of their accretion disks?

Abstract: We study here images of thin accretion disks around black holes and two classes of naked singularity spacetimes and compare these scenarios. The naked singularity models which have photon spheres have single accretion disk with its inner edge lying outside the photon sphere. The images and shadows created by these models mimic those of black holes. It follows, therefore, that further and more detailed analysis of the images and shadows structure in such case is needed to confirm or otherwise the existence of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 69 publications
5
87
0
Order By: Relevance
“…Our analysis demonstrated that the accretion disk will appear in a qualitatively similar way to a distant observer and only quantitative differences will be present in its size and radiation intensity. The problem was also revisited in [46], and the optical appearance of wormholes with a thin accretion disk was investigated in [47]. This work is a natural continuation of our previous studies examining the observable features of a thin disk around the strongly naked Janis-Newman-Winicour singularity.…”
Section: Introductionmentioning
confidence: 81%
“…Our analysis demonstrated that the accretion disk will appear in a qualitatively similar way to a distant observer and only quantitative differences will be present in its size and radiation intensity. The problem was also revisited in [46], and the optical appearance of wormholes with a thin accretion disk was investigated in [47]. This work is a natural continuation of our previous studies examining the observable features of a thin disk around the strongly naked Janis-Newman-Winicour singularity.…”
Section: Introductionmentioning
confidence: 81%
“…Following the same procedure discussed above, for such a photon, we obtain (see Eq. (4.12) of [59] for details)…”
Section: A Semi-analytic Ray-tracingmentioning
confidence: 99%
“…The solutions of Eqs. (14) and (15) can be obtained, using the transformations (11) and (12) on the Brans I metric (4), which we call here the Buchdahl solution [58]…”
Section: Jf Brans I ←→ Ef Bns (Or Jnw)mentioning
confidence: 99%
“…There could be other categories of hypothetical objects such as naked singularity (NS) and wormholes (WH) that are not ruled out either by theory or by experiment to date. On the contrary, there has been a recent surge of interest a e-mail: izmailov.ramil@gmail.com (corresponding author) in the study of their observational signatures, which include, but not limited to, the phenomena of accretion [2][3][4][5][6][7][8][9][10][11][12][13][14][15], gravitational lensing [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], shadow cast on the background of the thin accretion flow [32][33][34][35][36][37][38][39][40][41] and gravitational waves [42][43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%